Aboriginal Agency and Marginalisation in Australian Society - Moore, Terry (2014)
It is often argued that while state rhetoric may be inclusionary, policies and practices may be exclusionary. This can imply that the power to include rests only with the state. In some ways, the implication is valid in respect of Aboriginal Australians. For instance, the Australian state has gained control of Aboriginal inclusion via a singular, bounded category and Aboriginal ideal type. However, the implication is also limited in their respect. Aborigines are abject but also agents in their relationship with the wider society. Their politics contributes to the construction of the very category and type that governs them, and presses individuals to resist state inclusionary efforts. Aboriginal political elites police the performance of an Aboriginality dominated by notions of difference and resistance. The combined processes of governance act to deny Aborigines the potential of being both Aboriginal and Australian, being different and belonging. They maintain Aborigines’ marginality.